SISTEM INFORMASI PENDAFTARAN SIDANG DAN UPLOAD BERKAS PADA KEJAKSAAN NEGERI JAMBI BERBASIS WEB: Administration. MySQL, PHP, Sublime text, Xampp - Suana, Irma; Budiarti, Rike Limia; Lestari, Misya Indah (LP2M Universitas Nurdin Hamzah, 2025)
Abstract - Based on Law no. 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia. as stipulated in Article 30, namely in the field of crime, the prosecutor's office has the duties and authorities, one of which is to complete certain case files and for that reason they can carry out additional examinations before being delegated to the court which in its implementation is coordinated with investigators. Before conducting the trial, the Jambi District Attorney will determine in advance the registration of the trial. Based on the trial registration form process and the processing of whether the file has been accepted or not, the researchers found several problems, namely sloppy writing, making it difficult for employees to read, If there are some errors in writing, the file must be replaced with a new one and archiving which requires precision to be arranged with the arrangement. The purpose of this study is to design an information system for the trial registration form and upload the web-based trial file at the Jambi District Attorney's Office. The application is built using Sublime Text, Xampp, using the PHP programming language, and MySQL, This application produces information about the registration form activity program, Updates certain trial files online.